Novel elastic nanovesicles for cosmeceutical and pharmaceutical applications - Manosroi A. (2014)
Drug delivery systems using vesicular carriers such as liposomes or niosomes, have distinct advantages over conventional dosage forms because the vesicles can act as drug containing reservoirs and the modification of the vesicular compositions or surface properties can adjust the drug release rate and/or the affinity for the target site. The optimized elastic niosomal formulations for the topical non-invasive treatment of gene therapy and local pain or inflammation have been developed. The gel containing the novel Tween 61 elastic niosomes entrapped with DCFD (diclofenac diethylammonium) did not only show physical and chemical stability for 3 months, but also high fluxes through rat skin and high in vivo anti-inflammatory activity in rat ear edema assay. This optimized developed gel can offer a promising formulation for DCFD in the topical non-invasive treatment of inflammation. The enhancement of transdermal absorption of luciferase plasmid (pLuc) by entrapping in non-elastic vesicular formulations together with the application of the stratum corneum (SC) stripping and iontophoresis technique as well as the entrapment in elastic nanovesicles has also demonstrated. The elastic vesicles even without any application techniques can enhance the transdermal absorption of the plasmid. The pLuc entrapped in elastic niosomes gave higher fluxes than elastic liposomes, but no significance. The superior through skin delivery of pLuc by entrapping in niosomes with the application of iontophoresis can be used as a technique to deliver genetic materials via topical administration in gene therapy. However, although pLuc entrapped in elastic nanovesicles gave lesser fluxes than by iontophoresis application on the pLuc entrapped in non-elastic vesicles, elastic vesicles appeared to be a more promising approach with more practical use for topical gene delivery than the iontophoresis technique since no additional equipment is required.